Direct electrification of Rh/Al2O3 washcoated SiSiC foams for methane steam reforming: An experimental and modelling study. (5th May 2023) - Zheng, Lei; Ambrosetti, Matteo; Zaio, Francesca; Beretta, Alessandra; Groppi, Gianpiero; Tronconi, Enrico
Abstract: Electrified methane steam reforming (eMSR) is a promising concept for low-carbon hydrogen production. We investigate an innovative eMSR reactor where SiSiC foams, coated with Rh/Al2 O3 catalyst, act as electrical resistances to generate the reaction heat via the Joule effect. The novel system was studied at different temperatures, space velocities, operating pressures and catalyst loadings. Thanks to efficient heating, active catalyst and optimal substrate geometry, complete methane conversions were observed even at a high space velocity of 200000 Nl/h/kgcat . A specific energy demand as low as 1.24 kWh/Nm 3 H2, with an unprecedented energy efficiency of 81%, was achieved on a washcoated foam with catalyst density of 86.3 g/L (GHSV = 150000 Nl/h/kgcat, S/C = 4.1, ambient pressure). A mathematical model was validated against measured performance indicators and used to design an intensified eMSR unit for small scale H2 production. Highlights: Methane steam reforming via direct Joule heating of Rh/Al2 O3 washcoated SiSiC foam. High space velocities increase H2 productivity and overall energy efficiency. A predictive mathematical model shows excellent agreement with the experiments. Scale up calculations promise compact eMSR units with high H2 productivities.